Rekacipta Sistem Informasi Dan Pendaftaran Kurban Berbasis Web Pada Masjid Nurul Huda - Dirga Ananda, Gladian Dzaky; Suendri, Suendri (STMIK Banjarbaru, 2024)
Information technology has a significant impact on changing various aspects of life in the rapidly developing digital era, including in terms of sacrificial registration and mosque information management. The Nurul Huda Mosque is located in Hamlet 1 Gang BO Tanjung Morawa. Mosque agendas and finances, for example, are still managed manually, so the information provided to the public is incomplete or incorrect. To register as a sacrificial participant, someone must also come directly to the sacrificial committee's house. Creating a mosque information system and sacrificial registration so that the public can receive more accurate and transparent information without having to go to the sacrificial committee's house to register for sacrifices is the aim of this research. The waterfall method is used for system development. This research also uses a descriptive approach. The information system created by this research makes it easier for users to access information and register for sacrifices at the Nurul Huda Mosque.Keyword: Â Information System; Mosque; Sacrifice; Descriptive; WaterfallÂ AbstrakTeknologi informasi memiliki dampak yang signifikan terhadap perubahan berbagai aspek kehidupan di era digital yang berkembang pesat, termasuk dalam hal pendaftaran kurban dan manajemen informasi masjid. Masjid Nurul Huda berlokasi Di Dusun 1 Gang BO Tanjung Morawa. Agenda dan keuangan masjid, misalnya, masih dikelola secara manual, sehingga informasi yang diberikan kepada masyarakat tidak lengkap atau salah. Untuk mendaftar sebagai peserta kurban, seseorang juga harus datang langsung ke rumah panitia kurban. Menciptakan sistem informasi masjid dan pendaftaran kurban agar masyarakat dapat menerima informasi yang lebih akurat dan transparan tanpa harus mendatangi rumah panitia kurban untuk mendaftar kurban adalah tujuan penelitian ini dilakukan. Metode waterfall digunakan untuk pengembangan sistem. Penelitian ini juga menggunakan pendekatan deskriptif. Sistem informasi yang dibuat oleh penelitian ini memudahkan pengguna dalam mengakses informasi dan pendaftaran kurban di Masjid Nurul Huda.Â